Crustal Deformation in Southern California Constrained by Radial Anisotropy From Ambient Noise Adjoint Tomography - Wang, Kai; Jiang, Chengxin; Yang, Yingjie; Schulte‐Pelkum, Vera; Liu, Qinya (Geophysical research letters, 2020)
We build a new radially anisotropic shear wave velocity model of Southern California based on ambient noise adjoint tomography to investigate crustal deformation associated with Cenozoic evolution of the Pacific‐North American plate boundary. Pervasive positive radial anisotropy (4%) is observed in the crust east of the San Andreas Fault (SAF), attributed to subhorizontal alignment of mica/amphibole foliation planes resulting from significant crustal extension. Substantial negative anisotropy (6%) is revealed in the middle/lower crust west of the SAF, where high shear wave speeds are also observed. The negative anisotropy could result from steeply dipping amphibole schists in a shear zone developed during Laramide flat slab subduction. Alternatively, it could be caused by the crystal preferred orientation (CPO) of plagioclase, whose fast axis aligns orthogonally to a presumed subhorizontal foliation. The latter new mechanism highlights potentially complex CPO patterns resulting from different lithospheric mineralogy, as suggested by laboratory experiments on xenoliths from the region. Plain Language Summary The crust of Southern California has been shaped by complex tectonic processes through the evolution of the Pacific‐North America plate boundary. The mechanisms of crustal deformation in this area are not fully understood. We investigate the deformation regime by studying the seismic radial anisotropy of shear wave speed associated with mineral or structural orientations. Our work reveals pervasive positive radial anisotropy (VSH > VSV) in the crust and uppermost mantle, which is consistent with the tectonic setting of widespread and long‐term crustal extension of the western United States through the Cenozoic. Interestingly, we also observe strong negative anisotropy (VSH < VSV) in the lower crust west of the San Andreas Fault that has not been reported before. We interpret the positive anisotropy to be caused by the subhorizontal alignment of foliation planes of mica/amphibole whereas the negative one is potentially created by either steeply dipping amphibole schists or subhorizontal alignment of plagioclase. The distinct radial anisotropies across the transform plate boundary might indicate the importance of complex CPO patterns, resulting from different lithospheric mineralogy under the same strain regime. Key Points A radially anisotropic shear wave velocity model of Southern California is constructed from ambient noise adjoint tomography Positive radial anisotropy in the crust is caused by subhorizontal alignment of mica and amphibole associated with extensional tectonics Negative anisotropy west of the San Andreas Fault is attributed to steeply dipping amphibole schists or subhorizontally foliated plagioclase